Applying a Goal Programming Model to Support the Selection of Artifacts in a Testing Process. (30th December 2012) - Rodrigues da Silva, Andreia; Rodrigues de Almeida Júnior, Fernando; Pinheiro, Placido Rogerio
Abstract : This paper proposes the definition of a goal programming model for the selection of artifacts to be developed during a testing process, so that the set of selected artifacts is more viable to the reality of micro and small enterprises. This model was based on the IEEE Standard 829, which establishes a set of artifacts that must be generated throughout the test activities. Several factors can influence the definition of this set of artifacts. Therefore, in order to consider such factors, we developed a multicriteria model that helps in determining the priority of artifacts according to the reality of micro and small enterprises.